A dynamically optimized aircraft boarding strategy. (January 2017) - Zeineddine, Hassan
Abstract: Airline carriers, airports and passengers have common interests in expediting the aircraft boarding process for economical, operational, and customer satisfaction reasons respectively. Several boarding strategies have been proposed in the literature aiming to reduce the boarding time. Several theoretical models were able to achieve near optimum performance, but ignored the important aspect of allowing family and groups to board together in cliques. Some other models achieved top performance by pre-assigning passengers to seats, which deprived them from the essential privilege of choosing their own seats. The Dynamically Optimized Boarding strategy is proposed to shorten the boarding time, reduce on-board interferences, and allow passengers' cliques to proceed together to their reserved seats. Passengers are sequenced in a boarding queue based on their seats' positions, associated cliques, and the possibility of interferences, immediately after the last check-in. They are required to board the aircraft according to their positions in the queue. A technology-aided announcement process can help in guiding batches of passengers to a small pre-boarding area in order to aggregate before boarding the aircraft. A simulation-based study showed that the proposed strategy achieved a near-optimum performance without breaching the passengers' right to walk in cliques to their preferred seats.